The Influence of CSR, Leverage, Firm Size, Return on Assets, and Independent Board of Commissioners on Tax Planning - Munjiah, Fatihi; Wahyudi, Ickhsanto (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the influence of return on assets (ROA), corporate social responsibility (CSR), firm size, leverage, and independent board of commissioners on tax planning. The study consists of five independent variables: leverage proxied by Debt to Equity Ratio (DER), ROA (Return on Assets), CSR (Corporate Social Responsibility), firm size (Ln), and independent board of commissioners (IBC). The dependent variable, tax planning, is proxied by the Effective Tax Rate (ETR). The research sample includes 34 mining sector companies, but only 27 met the criteria. As a result, out of 170 total observations, only 135 were used as the sample size. The findings indicate that return on assets, corporate social responsibility, independent board of commissioners, and leverage have a negative effect on tax planning. Meanwhile, firm size has a positive effect on tax planning. Overall, this study provides empirical evidence on the significance of return on assets, corporate social responsibility, independent board of commissioners, leverage, and firm size in tax planning.